Regulating the Mechanical and Corrosion Properties of Mg-2Zn-0.1Y Alloy by Trace SiC with Different Morphologies - Furong Guo; Kaibo Nie; Kunkun Deng; Yanan Li (Crystals)
Traditional magnesium structural materials are used widely due to their light weight; however, their corrosion resistance is poor. In order to address this problem and improve the strength simultaneously, SiCp-, SiCnp-, and SiCnw-reinforced Mg-2Zn-0.1Y (wt. %, MZY alloy) matrix composites (SiC/MZY composites) with the same contents (0.3 wt. %) were prepared and extruded at low temperature in this paper. The effects of SiC morphology on the microstructure, mechanical properties and corrosion resistance of MZY alloy were studied. The results show that the grain size can be refined by adding SiC reinforcement. Compared with the unreinforced MZY alloy, the strengths of the SiC/MZY composites were all improved, with a yield strength of more than 440 MPa and an ultimate tensile strength of more than 450 MPa. However, only the corrosion rate of the composites reinforced by submicron SiCp was improved significantly. The hydrogen evolution corrosion rate (PH) was reduced by 81% relative to the MZY alloy. This can be attributed to the decreased galvanic corrosion pairs, as well as the decreased potential difference between the second phase and the matrix in the SiCp/MZY composite. Additionally, a compact product film on the surface of the SiCp/MZY composite can also protect the matrix. The materials prepared in this study showed excellent strength and high corrosion resistance at relatively low cost, providing valuable insights and design ideas for the development and application of those materials in marine and offshore engineering applications.